2013
DOI: 10.23986/afsci.6739
|View full text |Cite
|
Sign up to set email alerts
|

Changes in maize silage fermentation products during aerobic deterioration and effects on dry matter intake by goats

Abstract: Chemical and microbiological changes occurring during aerobic exposure of maize silages and their influence on dry matter (DM) intake and preference by goats were evaluated. Eight maize silages differing in DM content, chopping length and compaction pressure were used for the study. After opening, silages were exposed to air for 8 days (d). In 2-d intervals, silage was stored anaerobically for use in preference trials. During the experimental phase, each possible two-way combination of the five silages (d0, d2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
88
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(104 citation statements)
references
References 33 publications
11
88
2
3
Order By: Relevance
“…The reduction in intake is justiied due to the taste and odor of silage. In other studies, DMI was negatively correlated with acetic acid [19]. …”
mentioning
confidence: 96%
See 4 more Smart Citations
“…The reduction in intake is justiied due to the taste and odor of silage. In other studies, DMI was negatively correlated with acetic acid [19]. …”
mentioning
confidence: 96%
“…In Table , it is observed that after exposure to air over time 8 and 9 days , there was a reduction in the WSC content of corn silage and an increased DM content [8]. The sugarcane silages showed an increase in the NDF and CP contents and reduced lignin ADL and non-ibrous carbohydrate NFC contents [19]. These changes in the chemical composition of silages can interfere on intake and digestibility of silages.…”
Section: Cropmentioning
confidence: 99%
See 3 more Smart Citations